A ḥadīth collection over the generations: the transmission of Ṣaḥīḥ Ibn Ḥibbān - Muhammad Fawwaz Muhammad Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study of ḥadīth scholarship, even if concentrating ḥadīth corpus, or even extracting the transmission of ḥadīth collections, has faced growing criticism. Many scholars of ḥadīth have no lack of confidence about the preservation of ḥadīth collections, while others have thoughtfully been sceptical. The discussion of the “authenticity” of authorship of ḥadīth collections, Arabic literature furnishes with a chain of transmitters for texts made about the past. Alongside both famous Ṣaḥīḥayn of al-Bukhārī and Muslim, Ibn Ḥibbān al-Bustī (d. 354/965) - a scholar from Lashkar Gah, Afghanistan - compiled at least one gigantic ḥadīth collection usually regarded as the last collection of this ‘Ṣaḥīḥ movement’. Among the eighty-plus works that Ibn Ḥibbān’s biographers say he wrote is his famous ḥadīth collection named “alMusnad al-Ṣaḥīḥ ʿalā al-Taqāsim wa al-Anwāʿ min ghayr wujūd qaṭʿ fī sanadihā walā thubūt jarḥ fī nāqilīhā.” The Ṣaḥīḥ, like the many existing ḥadīth compilations, was handed down to succeeding generations by chains of authority. What follows is an explanatory study of the transmission of Ṣaḥīḥ Ibn Ḥibbān in post-hadith compilation literatures to which his fame is principally due. A library-based research which focuses on descriptive analytical method is used in this study. This study also aims to examine some conceptual grounds for the exploration by looking into the literary dimension of hadith literatures. Explaining the transmission of Ibn Ḥibbān’s Ṣaḥīḥ is demanding despite his noble status which is required in recognizing that the early and canonical ḥadīth collection was very limited in dissemination. Conclusion of this study notes that the availability of transmission is central for the assessment of the well-preserved book and the role of isnād and certain ḥadīth literatures are vital in transmitting and preserving the Ṣaḥīḥ.